ANALISIS KETIMPANGAN SEKTORAL, KETIMPANGAN SPASIAL, DAN PERTUMBUHAN EKONOMI KABUPATEN GUNUNGKIDUL TAHUN 2005-2010 - , Asar Janjang Riyanti; , Prof. Dr. Tri Widodo, M.Ec.Dev., ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Development issues such as sectoral inequality will occur when the development of a sector can not encourage other sectors to co-evolve anyway. Sectoral inequality is very likely to occur in all regions. Spatial inequality may also occur in areas experiencing sectoral inequality. The research aims to analyze the sectoral inequality and spatial inequality Gunungkidul of 2005-2010 and analyze the relationship between economic growth and sectoral inequality in Gunungkidul 2005-2010. The variables used are based Gunungkidul GDP at constant 2000 prices and GDP at constant prices based district in 2000. Types of data using a panel data. The analysis tool used are the coefficient of variation, Geographic Information Systems (GIS), particularly ESRI ArcView, Pearson product moment correlation, panel data regression, and descriptive analysis. This result indicated that there is inequality in Gunungkidul sector over the period 2005-2010. Sectoral inequality shows the results tended to decrease during the study period. The whole district is in the southern zone, spatially having sectoral inequality relatively higher high, the two districts are north zone has sectoral imbalances are relatively high, while the sectoral inequality are relatively lower in districts that are connected and clustered in the middle zone and north. The economic growth of 2005-2010 Gunungkidul negatively related to sectoral inequality indicated by the Pearson correlation coefficient of -0290, but the relationship is not very strong. GDP per capita variable sub i in Gunungkidul negative and significant effect on the level of inequality coefficient of variation indicating sectoral sub i in Gunungkidul.